2018
DOI: 10.1111/imig.12517
|View full text |Cite
|
Sign up to set email alerts
|

Integration and Retention of Refugees in Smaller Communities

Abstract: While advanced economies attempt to pursue a regionalized immigration policy, which aims at shifting migration flows away from the most popular urban centre destinations to smaller communities, the experiences of immigrants settling in such locations remains underexplored. This research provides timely knowledge of refugee labour market integration in smaller communities, using Newfoundland and Labrador's provincial capital, St. John's, as an example of such communities. The article examines the resettlement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…For example, a small-scale study on refugees living in the northern Australian city of Brisbane found that local language proficiency is not a significant predictor of employment (Correa-Velez et al, 2015). Such findings contradict prior research that found strong local language skills to be crucial for refugees' securing employment (Arendt et al, 2020;de Vroome & van Tubergen, 2010;Fang et al, 2018;Khawaja & Hebbani, 2018). These inconsistencies in the literature raise the need to investigate the roles of language proficiency for refugees' economic integration in terms of employment outcomes.…”
Section: Existing Literaturementioning
confidence: 90%
“…For example, a small-scale study on refugees living in the northern Australian city of Brisbane found that local language proficiency is not a significant predictor of employment (Correa-Velez et al, 2015). Such findings contradict prior research that found strong local language skills to be crucial for refugees' securing employment (Arendt et al, 2020;de Vroome & van Tubergen, 2010;Fang et al, 2018;Khawaja & Hebbani, 2018). These inconsistencies in the literature raise the need to investigate the roles of language proficiency for refugees' economic integration in terms of employment outcomes.…”
Section: Existing Literaturementioning
confidence: 90%
“…Currently, a lack of connection exists between proactive labour organizations, societal initiatives, government policy, academic research and the lived experiences of refugees, which risks the repetition of actions and endeavours in both practice and research (see also Fang et al, 2018). It is therefore vital to give shape to an infrastructure that can connect societal partners (including employers and policymakers) and academics with refugee perspectives (for an example, see the case of Refugee Academy 2 , Ghorashi, 2020).…”
Section: Conclusion: Rethinking the Integration Approachmentioning
confidence: 99%
“…Employers have also become vocal advocates for immigration in Atlantic Canada, from fish processing plants to video game developers (Marschke et al 2018;Pottie-Sherman and Lynch 2019). Yet, retaining newcomers is an ongoing challenge due to a lack of full-time employment, limited education, recreational and cultural opportunities, social isolation, and exclusion (Randall et al 2014;Fang et al 2018;Tastsoglou and Sevgur 2019). Across the region, municipalities, non-state organizations, and the private sector are working to convince newcomers to "live, work, and stay."…”
Section: Conceptualizing Aspiring Gatewaysmentioning
confidence: 99%
“…This program intends to generate more permanency in non-traditional destinations, which may be accustomed to "small trickle" of temporary workers and have gotten "used to them coming and leaving," as one NL has the lowest immigrant population in Canada, and while most immigrants in the province reside in St. John's, immigrants comprise only four percent of the population in that city (Statistics Canada 2017). With an unfriendly labor market, challenging weather, and geographic isolation, NL struggles to retain immigrants and refugees (Fang et al 2018).…”
Section: Private Sectormentioning
confidence: 99%